Modes of neighbourhood embeddedness in three multi-ethnic neighbourhoods in Lisbon: an exploratory analysis - Fonseca, Maria Lucinda (2013)
The role of urban neighbourhoods in social cohesion has been extensively debated in recent times, both in academic and political circles. This paper explores different modes of coexistence and neighbourhood embeddedness in three multi-ethnic neighbourhoods in the Lisbon Metropolitan Area. Using factor and cluster analysis, with data collected in a survey of the native and immigrant population and drawing upon complementary qualitative data from focus groups with key actors in each neighbourhood, five modes of neighbourhood embeddedness are identified. These modes serve to enhance our understanding of the nature of social interactions and social networks between and within groups. A geographical perspective is adopted incorporating possible effects relating to the characteristics of the neighbourhood as well as the socio-ethnic and demographic profiles of the respondents.